Diagnóstico de situación de la docencia y el ambiente educativo existente en la Escuela de Medicina Universidad de Chile 2013, según opinión de sus alumnos de 2º a 7º año 2013 - Gómez M., Patricia; Lavín B., Alejandra; Latorre G., Patricia; Cacho O., Javier; Samaniego E., Francisco; Rivas M., Catalina (Revista Hospital Clínico Universidad de Chile, 2014)
The Faculty of Medicine of the University of Chile has developed a program, where students play an important role colaborating with their teachers in research. Traditionally it has been related to basic and/or clinical research. We present here an innovation: the participation of students in educational research. Medical students from different learning stages participated actively planning and performing this research, and they were indeed crucial for its success. The study shown here, is intended to favour the development of a “Continous Joint Educational Research Program”, which main goal would be to identify eventual teaching problems in order to develop prompt and adecuate solutions to continously improve the quality of medical education. The diagnosis made by the students’ opinions is only the first step of this project. Teachers’ opinions need to be considered also in a second stage. Learning outcome’s evaluation was identified by medical students as being one of the most problematic areas. A great number of them confess “traumatic experiences” in this field, some of which are described here as a mean of making teachers aware of the problem, leading them to seek for teaching and evaluation methodologies capacitation.